FOR WORK / BEKISTING PADA BANGUNAN GEDUNG BERTINGKAT - Darma, Budhi (Gema Teknologi, 2010)
Budhi Dharma, in this paper explain that to get a good concrete structure form, need the existence of making of work form (bekisting) the goodness. In this case accuration, strength and also the supporter structure of having to enough of strength. To facilitate installation and also time efficiency in execution of unloading and installation need a correct and good construction. Keywords:bekesting, structure strength